ANALISIS KOMPETENSI SISWA TENTANG KESEHATAN, KESELAMATAN KERJA, DAN LINGKUNGAN HIDUP (K3LH) DI SEKOLAH MENENGAH KEJURUAN - Maria Veronika Simanjuntak, - (2018)
Siswa Sekolah Menengah Kejuruan (SMK) sebagai pekerja muda memasuki tempat kerja melalui praktek kerja industri, pekerja paruh waktu, dan pekerja setelah lulus sekolah yang memiliki risiko kecelakaan kerja yang tinggi sehingga siswa harus memiliki keterampilan dasar tentang K3LH. Berdasarkan studi pendahuluan 75 siswa (89.29%) pernah mengalami kecelakaan kerja kategori ringan di sekolah maupun di indsutri. Kecelakaan rentan terjadi ketika pekerja tidak memiliki kompetensi yang baik. Tujuan dari penelitian ini adalah mengidentifikasi kompetensi siswa tentang Kesehatan, Keselamatan Kerja, dan Lingkungan Hidup (K3LH) di SMK, peranan guru dalam pelaksanaan K3LH di sekolah, dan peranan supervisor dalam mengimplementasikan K3LH di industri. Kompetensi termasuk pengetahuan, keterampilan, dan pengalaman tentang K3LH siswa SMK. Desain penelitian ini adalah kuantitatif desktiptif, menggunakan instrumen tes dan angket untuk mengidentifikasi kompetensi siswa dan wawancara untuk mengidentifikasi peranan guru dan supervisor. Responden penelitian adalah 124 siswa dan empat guru berasal dari empat sekolah, dua sekolah negeri dan dua sekolah swasta serta tiga supervisor dari industri. Hasil analisis kompetensi siswa tentang K3LH dibagi dalam tiga kategori. Pertama, kategori tinggi dengan perolehan nilai > 70.32 sebanyak 22 siswa (15.49%). Kedua, kategori sedang dengan perolehan nilai 46.41 ≤ x ≤ 70.32 sebanyak 100 siswa (70.42%). Ketiga, kategori rendah dengan perolehan nilai > 46.41 sebanyak 20 orang (14.08%). Rata-rata kompetensi siswa tentang K3LH dalam kategori sedang. Peranan guru dalam proses pelaksanaan K3LH siswa SMK sesuai dengan kurikulum sekolah dan peranan supervisor sesuai dengan peraturan di industri tetapi belum memenuhi standar K3LH. ;---Vocational High School students, as young workers whom enter the workplace through industrial working practice, part-time workers and fresh-graduate workers, have a high risk of working's accident. This condition makes the students must have basic skills about Environment, Safety, and Occupational Health. Based on previous study, 75 students (89.29%) had non-fatal injury categories in the school or industry. The accidents can easily happen whenever the workers have a weak competency. The goal of this research is to identify students' competency towards Environment, Safety, and Occupational Health in Vocational High School, teacher's role in excecuting Environment, Safety, and Occupational Health in the school, and supervisor's role in implementing Environment, Safety, and Occupational Health in the industry. The competencies involve knowledge, skills, and experiences that related with Environment, Safety, and Occupational Health. The design of this research is a descriptive quantitative. Test and questionnaire are used to identify students' competency, while interview is used to identify teacher's and supervisor's role. The respondent of this research are 124 students and 4 teachers from four schools. The schools are categorized into two public schools and two private schools. There are also 3 supervisors whom become respondent of this research too. The analysis result of students' competencies are divided into three categories. First ishigh category with the score is above 70.32. Second is middle category with the score is between 46.41 and 70.32. Last category is low category with the score is below 46.41. There are 22 students (15.49%) on the first category, 100 students (70.42%) on the second category, and 20 students (14.08%) on the last category. The average students' competency towards Environment, Safety, and Occupational Health is in the middle category. Teacher's role in excecuting Environment, Safety, and Occupational Health process based on school curriculum and supervisor's role based on the industy's rules are unfortunately not meeting the standard of Environment, Safety, and Occupational Health.